COMPUTER DIAGNOSTICS OF CARS - Mukimova Davlatkhon Karimovna; Abdupattayev Bekmurod Bakhrom ugli (Лучшие интеллектуальные исследования, 2023)
The timely detection of abnormalities and faults at the earliest stage - a guarantee of stable operation and durability of the vehicle. To achieve this goal, computer diagnostics of cars is carried out. This is a wide range of diagnostic activities carried out with the help of computer technology aimed at detecting malfunctions by reading information from the sensors located at the main vehicle nodes.